Compact instrumentation and (analytical) performance evaluation for laser-induced breakdown spectroscopy. Issue 1 (2nd January 2019) - Guo, Guangmeng; Niu, Guanghui; Lin, Qingyu; Wang, Shuai; Tian, Di; Duan, Yixiang
Abstract: In this work, a compact laser induced breakdown spectroscopy (LIBS) instrument was developed based on a high energy lightweight laser source and an integrated control system, making the instrument well integrated and convenient to use. The instrument has a compact size of 45 cm ×36 cm ×45 cm and weights only 21 kg. The spectrometer operated in the range from 180 to 850 nm with a resolution of 0.15 nm, which was customizable. The client software was customized as the interface for process control and data acquisition. Some procedures were carried out to evaluate the performance of this instrument. First, the laser source worked at an average energy value of 116 mJ, with a relative standard deviation of 2.58% for 9999 laser pulses after continuously running for 3 hr. Second, qualitative analysis was performed to show the classification ability for copper mineral samples. Besides, the calibration curves were achieved by using the emission lines of Cu (I) 510.55 nm, Cu (I) 521.82 nm, Zn (I) 307.58 nm, and Zn (I) 328.23 nm, with the correlation coefficient R 2 of 0.97432, 0.9826, 0.97286, and 0.98176, and the limit of detection was shown to be 0.0365%, 0.0399%, 39.581 µg·g −1, and 47.081 µg·g −1, respectively. According to the evaluation results, the compact laser source was excellent for stable measurement and the proposed compact instrument performed well for the qualitative and quantitative elemental analysis with satisfied results. Therefore, the proposed LIBS instrument has potential to find applications in a variety of circumstances.